PENGUJIAN INTEGRITAS DATA MENGGUNAKAN ALGORITMA MD5 - Buana, Rendi Gayu (DINAMIKA DOTCOM, 2012)
Often the integrity of the data did not change as the original caused by many things such as due to a virus and modified by others, and most people do not pay attention to the integrity of the data so that the data is not complete as the original, then the data can not be used. Thus this study to test the integrity of the data using the MD5 algorithm.The methods in scientific writing using the MD5 algorithm, which is one of the cryptographic functions that can generate a unique code of a file or files.MD5 can detect changes in the contents of a file even if the change is very small. Changes can be made up of addition, subtraction or change of the contents of a file. Speed MD5 generate code that is the larger the file size the longer the generated code MD5.Â Key words: Testing, Integrity, Data, Algorithms, MD5